Description of a new thermal species of the genus Hyalella from Peru with molecular phylogeny of the family Hyalellidae (Crustacea, Amphipoda). - Tomikawa, K. (2023)
In recent years, the impact of rising water temperatures associated with global warming on cold-water freshwater organisms has become a major issue, and understanding the physiological and ecological elements that support temperature limits is essential for the conservation biology of freshwater organisms. We describe a new species of thermophilic hyalellid amphipod, Hyalella yashmara sp. nov. from the Peruvian hot spring Baños del Inca Cajamarca and this could potentially contribute to understanding the high temperature preference of these. We found that this new species can live in water temperatures ranging from 19.8 to 52.1°C, that, to our knowledge, is the highest recorded habitat temperature of amphipods. Hyalella yashmara sp. nov. is most similar to H. meinerti Stebbing, 1899 from Peru. However, this new species differs from the latter in features of gnathopods 1 and 2, sternal gills, uropod 3 and telson. A detailed morphological comparison between Hyalella yashmara sp. nov. and Peruvian species is also provided. Our molecular phylogenetic analyses based on the nuclear 28S rRNA and mitochondrial cytochrome c oxidase subunit I (COI) gene sequences strongly support the monophyly of Hyalellidae (=Hyalella). Since Hyalellidae was found to form a sister group with Chiltoniidae, these two families were expected to have originated from a common ancestor that invaded freshwater habitats from marine environments when the continents of South America, Africa and Australia were united as Gondwana. Our findings suggest that the South American species of Hyalella are not monophyletic and that the North American species are likely to share a most recent common ancestor with H. yashmara sp. nov.